2001
DOI: 10.1093/jn/131.3.1041s
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Inhibition of Chemical Toxicity and Carcinogenesis by Diallyl Sulfide (DAS) and Related Compounds from Garlic

Abstract: Diallyl sulfide (DAS) is a flavor compound derived from garlic and is sequentially converted to diallyl sulfoxide (DASO) and diallyl sulfone (DASO(2)) by cytochrome P(450) 2E1 (CYP2E1). These compounds have been shown to reduce the incidence of a multitude of chemically induced tumors in animal models. The impediment of phase I activation of these carcinogens is hypothesized to be accountable for the reduction in tumor incidence. Indeed, DAS, DASO and DASO(2) are competitive inhibitors of CYP2E1. DASO(2), in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
82
0
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 176 publications
(86 citation statements)
references
References 60 publications
2
82
0
2
Order By: Relevance
“…Garlic (Allium sativum L.), is widely used as foodstuff and medicine throughout the recorded history (5). Based on epidemiologic, clinical, and laboratory studies we have indicated that Allium vegetables and/or their constituents contain biological activities that stimulate immune function Diallyl sulfide induces cell cycle arrest and apoptosis in HeLa human cervical cancer cells through the p53, caspase-and mitochondria-dependent pathways (6,7), reduce the risk of cardiovascular diseases (8)(9)(10)(11), change blood glucose level (12,13) anti-microbial, viral and fungal infections (14)(15)(16), anti-aging effects (17,18), anti-cancer function (19)(20)(21) and anti-tumorigenesis effects (22). Increasing evidences has suggested that the mechanism of anti-cancer action of garlic compounds may involve modulation of signal transduction pathways (23).…”
Section: Introductionmentioning
confidence: 99%
“…Garlic (Allium sativum L.), is widely used as foodstuff and medicine throughout the recorded history (5). Based on epidemiologic, clinical, and laboratory studies we have indicated that Allium vegetables and/or their constituents contain biological activities that stimulate immune function Diallyl sulfide induces cell cycle arrest and apoptosis in HeLa human cervical cancer cells through the p53, caspase-and mitochondria-dependent pathways (6,7), reduce the risk of cardiovascular diseases (8)(9)(10)(11), change blood glucose level (12,13) anti-microbial, viral and fungal infections (14)(15)(16), anti-aging effects (17,18), anti-cancer function (19)(20)(21) and anti-tumorigenesis effects (22). Increasing evidences has suggested that the mechanism of anti-cancer action of garlic compounds may involve modulation of signal transduction pathways (23).…”
Section: Introductionmentioning
confidence: 99%
“…Since MNNG induces O 6 -methylguanine leading to G:C-to-A:T mutations (38), we suggest that nobiletin may not enhance the repair activity against O 6 -methylguanine or promote error-free translesion bypass across the lesion. Instead, we suggest that nobiletin may suppress the genotoxicity of NNK by inhibiting the activity of CYP (P-450) enzymes involved in the metabolic activation of NNK (39)(40)(41). In fact, 8-methoxypsoralen, a speciˆc-inhibitor of CYP2A, similarly suppressed the genotoxicity of NNK in the presence of S9 enzymes (23).…”
Section: Discussionmentioning
confidence: 78%
“…DPI, an inhibitor of NADPH oxidase complex (12,17,38), inhibited most of the oxidase activity in E2 and M1 cells, consistent with the action of the inhibitor. DAS, a CYP2E1 inhibitor (3,54), halved the oxidase activity in E2 cells, suggesting involvement of CYP2E1, at least in part, in the stimulation of NADPH oxidase activity in E2 cells, but it had no effect on the oxidase activity in M1 cells, reflecting the absence of CYP2E1. LPS/LBP treatment raised the oxidase activity in both E2 and M1 cells compared with corresponding untreated cells (Fig.…”
Section: Effects Of Increased Cyp2e1 Expression On Nadph Oxidase Actimentioning
confidence: 96%